A B2 SINE insertion in the Comt1 gene (Comt1(B2i)) results in an overexpressing, behavior modifying allele present in classical inbred mouse strains. - Kember, R; Fernandes, C; Tunbridge, E; Liu, L; Payá-Cano, J; Parsons, M; Schalkwyk, L (2010)
Catechol-O-methyltransferase (COMT) is a key enzyme for dopamine catabolism and COMT is a candidate gene for human psychiatric disorders. In mouse it is located on chromosome 16 in a large genomic region of extremely low variation among the classical inbred strains, with no confirmed single nucleotide polymorphisms (SNPs) between strains C57BL/6J and DBA/2J within a 600-kB window. We found a B2 SINE in the 3' untranslated region (UTR) of Comt1 which is present in C57BL/6J (Comt1(B2i)) and other strains including 129 (multiple sublines), but is not found in DBA/2J (Comt1(+)) and many other strains including wild-derived Mus domesticus, M. musculus, M. molossinus, M.castaneus and M. spretus. Comt1(B2i) is absent in strains closely related to C57BL/6, such as C57L and C57BR, indicating that it was polymorphic in the cross that gave rise to these strains. The strain distribution of Comt1(B2i) indicates a likely origin of the allele in the parental Lathrop stock. A stringent association test, using 670 highly outbred mice (Boulder Heterogeneous Stock), indicates that this insertion allele may be responsible for a difference in behavior related to exploration. Gene expression differences at the mRNA and enzyme activity level (1.7-fold relative to wild type) indicate a mechanism for this behavioral effect. Taken together, these findings show that Comt1(B2i) (a B2 SINE insertion) results in a relatively modest difference in Comt1 expression and enzyme activity (comparable to the human Val-Met polymorphism) which has a demonstrable behavioral phenotype across a variety of outbred genetic backgrounds.